Develop the Speaking Skills of B1 Level Students: Mengembangkan Kemampuan Berbicara Siswa Level B1 - Xoldorova , Xoldorova (Indonesian Journal of Education Methods Development, 2024)
This study delves into the enhancement of speaking skills in B1 level students, emphasizing the pivotal role of communicative competence. Through an exhaustive literature analysis, diverse strategies are explored to discern key elements contributing to language acquisition success at this intermediate level. The methods section delineates practical approaches for educators, integrating interactive activities and motivation techniques. Results showcase the positive outcomes of implementing these methods, paving the way for a nuanced discussion on the implications of the findings. In conclusion, the article offers valuable suggestions for further research and provides practical recommendations to empower language educators globally. Highlights: Effective Strategies for B1 Students: Explore and identify key elements crucial for successful language acquisition at the B1 level, emphasizing the importance of communicative competence. Practical Approaches for Educators: Outline actionable methods that educators can implement, incorporating interactive activities and motivation techniques to enhance students’ speaking skills. Positive Outcomes and Implications: Present and discuss the results of applying these methods, highlighting the positive outcomes and providing insights into the broader implications for language education. Keywords: Speaking Skills, B1 Level, Language Acquisition, Communicative Competence, Interactive Activities